2016
DOI: 10.1007/s00774-016-0778-3
|View full text |Cite
|
Sign up to set email alerts
|

4-Phenyl butyric acid prevents glucocorticoid-induced osteoblast apoptosis by attenuating endoplasmic reticulum stress

Abstract: Apoptosis of osteoblasts triggered by high-dose glucocorticoids (GCs) has been identified as a major cause of osteoporosis. However, the molecular mechanisms underlying GC-induced osteoporosis remain elusive. This study was conducted to make clear the mechanism of GC-induced osteoblast apoptosis and to examine whether reduction of ER stress by 4-PBA inhibited osteoblast apoptosis. After treatment with dexamethasone (Dex) or hydrocortisone, cell viability was assessed using an MTT assay. Flow cytometry was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 37 publications
2
14
0
Order By: Relevance
“…Disrupting this balance has certain harmful effects; for instance, an increased production of ROS may inhibit the differentiation of osteoblasts ( 24 , 37 ). The results of the present study indicated that ER stress was activated by DEX via increasing the expression of the associated proteins ATF4 and CHOP, which is in accordance with the study by Yang et al ( 30 ). In addition, the results of the autophagy analysis indicated that DEX caused autophagy by increasing the levels of Beclin1 and LC3BII, and by decreasing the expression of P62.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Disrupting this balance has certain harmful effects; for instance, an increased production of ROS may inhibit the differentiation of osteoblasts ( 24 , 37 ). The results of the present study indicated that ER stress was activated by DEX via increasing the expression of the associated proteins ATF4 and CHOP, which is in accordance with the study by Yang et al ( 30 ). In addition, the results of the autophagy analysis indicated that DEX caused autophagy by increasing the levels of Beclin1 and LC3BII, and by decreasing the expression of P62.…”
Section: Discussionsupporting
confidence: 93%
“…ER stress is a state in which the homeostasis of protein folding load and the capacity of the ER is disrupted ( 28 , 29 ). Excess ER stress has been demonstrated in MC3T3-E1 cells after treatment with DEX, and has also been proven to induce apoptosis ( 30 , 31 ). Autophagy is known to be a self-degradative process that is important for balancing sources of energy at critical times during development, and in response to nutrient stress ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Release of cytochrome-C, an apoptogenic protein, by activated mitochondria into the cytosol triggers caspase proteases that degrade cells via the mitochondrial pathway [ 3 , 22 , 23 ]. Bax is a key regulator of the mitochondrial pathway of apoptosis that accumulates at distinct foci on the mitochondrial surface to undergo a conformational change, oligomerize, and mediate cytochrome-C translocation [ 24 ]. AIF induces caspase-independent fragmentation of chromosomal DNA to amplify apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Although ER stress correlates with various diseases, the role of ER stress in the pathogenesis of GC-induced ONFH remains unclear. A few studies have indicated that treatment with GCs leads to ER stress and results in various changes, including dysfunction and apoptosis of osteoblasts, osteocytes, and trabecular-meshwork cells (34,44,45). Nevertheless, few studies have focused on the GC-induced EC apoptosis mediated by the ER stress signaling pathway.…”
Section: Introductionmentioning
confidence: 99%